2020
DOI: 10.1002/iub.2336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic variations in Acads gene on the risk of chronic obstructive pulmonary disease

Abstract: Short‐chain acyl‐CoA dehydrogenase (SCAD), encoded by the Acads gene, functions in the mitochondrial β‐oxidation of saturated short‐chain fatty acids. SCAD deficiency results in mitochondrial dysfunction, which is one underlying biological mechanism of chronic obstructive pulmonary disease (COPD) pathogenesis. In this case–control study, we aimed to examine the effects of Acads gene polymorphisms on the susceptibility to COPD. A total of 16 tagging single‐nucleotide polymorphisms (SNPs) in Acads gene region wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…These studies showed that ECMs were involved in the process of COPD, but whether it was related to their acetylation difference needs to be investigated further. Acyl-CoA dehydrogenase short chain (ACADS) may be a risk factor for COPD ( 53 ). Short chain acyl-CoA dehydrogenase (SCAD) is encoded by ACADS, and ACADS gene variants cause the mutation of SCAD, leading to mitochondrial damage and excessive production of reactive oxygen species (ROS) ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that ECMs were involved in the process of COPD, but whether it was related to their acetylation difference needs to be investigated further. Acyl-CoA dehydrogenase short chain (ACADS) may be a risk factor for COPD ( 53 ). Short chain acyl-CoA dehydrogenase (SCAD) is encoded by ACADS, and ACADS gene variants cause the mutation of SCAD, leading to mitochondrial damage and excessive production of reactive oxygen species (ROS) ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%